A Cross-Sectional Study to Find Out the Incidence and Associated Risk Factors of Pressure Injury Acquired in the ICU Unit at Pt. B.D. PGIMS, Rohtak - Kavita Choudhary; Pawan Kumar Singh; Kunal (International Journal of Emergency and Trauma Nursing and Practices, 2025)
Pressure injuries, also known as pressure ulcers or bedsores, remain a major concern in intensive care units (ICUs) due to their adverse impact on patient outcomes and healthcare quality. This study aimed to assess the incidence and associated risk factors of pressure injuries among patients admitted to the ICU at Pt. B.D. Sharma Post Graduate Institute of Medical Sciences (PGIMS), Rohtak. A descriptive cross-sectional design was adopted, and data were collected from 100 ICU patients using a structured clinical assessment tool and the Braden risk assessment scale. Demographic and clinical variables such as age, gender, duration of ICU stay, mobility, nutritional status, moisture exposure, comorbidities, and Braden scores were analyzed. The findings revealed that 27% of patients developed pressure injuries during their ICU stay. A statistically significant association was observed between pressure injury occurrence and factors such as low Braden score (≤16), immobility, and moisture exposure (p<0.05). Although variables like nutritional status and comorbidities did not show significant associations, they remain clinically relevant for overall patient management. The study highlights the importance of early identification of at-risk patients and implementation of targeted nursing interventions, including regular repositioning, effective moisture management, nutritional optimization, and use of pressure-relieving devices. These results underscore the need for structured prevention protocols and ongoing staff education to reduce the incidence of pressure injuries in critical care settings and improve patient outcomes.
Keywords: Braden Scale; Intensive care unit; Nursing Interventions; Risk factors; pressure injuries